Extraordinary Strong Band‐Edge Absorption in Distorted Chalcogenide Perovskites. Issue 5 (29th January 2020) - Nishigaki, Yukinori; Nagai, Takayuki; Nishiwaki, Mitsutoshi; Aizawa, Takuma; Kozawa, Masayuki; Hanzawa, Kota; Kato, Yoshitsune; Sai, Hitoshi; Hiramatsu, Hidenori; Hosono, Hideo; Fujiwara, Hiroyuki
Abstract : All existing solar cell materials including hybrid perovskites show rather small absorption coefficient ( α ) of ≈10 4 cm −1 in the bandgap ( E g ) transition region. The weak band‐edge light absorption is an essential problem, limiting conversion efficiency particularly in a tandem solar cell. Herein, all distorted chalcogenide perovskites (BaZrS3, SrZrS3, BaHfS3, and SrHfS3 ) are found experimentally to exhibit extraordinary high α exceeding 10 5 cm −1 near E g, indicating the highest band‐edge α among all known solar cell materials. The giant absorption in the E g region, which is consistent with the first principles, arises from the intense p–d interband transition enabled by dense S 3p valence states. For solar cell application, low‐gap BaZrS3 derivatives, Ba(Zr, Ti)S3 and BaZr(S, Se)3, are further synthesized. Among the possible candidates of top‐cell materials, an earth‐abundant and nontoxic Ba(Zr, Ti)S3 alloy shows great potential, reaching a maximum potential efficiency exceeding 38% in a chalcogenide perovskite/crystalline Si tandem architecture. Abstract : Chalcogenide perovskites (BaZrS3, SrZrS3, BaHfS3, and SrHfS3 ) synthesized by solid reaction processes exhibit an extraordinary strong light absorption of >10 5 cm −1 in the bandgap region. The superior optical characteristics originate from the unique band structures of the chalcogenide perovskites, making the materials ideal for the top cell in tandem solar cell devices.